2013
DOI: 10.1260/0144-5987.31.5.771
|View full text |Cite
|
Sign up to set email alerts
|

De-Oiled Rice Bran as a Source of Bioethanol

Abstract: Bioethanol is regarded as one of the most promising biofuel from renewable sources. The development of ethanol production from lignocellulosic material is thus considered as the second-generation biofuel technology. Lignocelluloses account for the majority of the total biomass present in the world. To initiate the production of industrially important products from cellulosic biomass, bioconversion of the cellulosic components into fermentable sugars is necessary. A variety of microorganisms including bacteria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Banerjee et al (2009) studied effect of temperature on bioethanol production from rice husk and found maximum production at 30°C. Beliya et al (2013) found 25°C was optimum temperature for bioethanol production from deoiled rice bran.…”
Section: Effect Of Temperature Variations On Bioethanol Productionmentioning
confidence: 91%
See 1 more Smart Citation
“…Banerjee et al (2009) studied effect of temperature on bioethanol production from rice husk and found maximum production at 30°C. Beliya et al (2013) found 25°C was optimum temperature for bioethanol production from deoiled rice bran.…”
Section: Effect Of Temperature Variations On Bioethanol Productionmentioning
confidence: 91%
“…Pandey et al (2013) used azolla as a source of bioethanol. Beliya et al (2013) used deoiled rice bran for bioethanol production. Tiwari et al (2014) produced fuel ethanol from waste fruits.…”
Section: Introductionmentioning
confidence: 99%
“…The bioethanol yield had a value of 0.42 g/g and productivity of 0.173 g/L/h. Biological pretreatment with the fungus Aspergillus niger increased the ethanol production by P. kudriavzevii RCEF4907 in the study of Beliya et al [58]. Under optimum conditions of temperature (25 • C), pH (6.5) and nutrients (addition of 1% Urea), the strain was able to produce 11.4% ethanol.…”
Section: Production Of Bioethanolmentioning
confidence: 97%
“…% from the sugar beet pulp (Rezic et al, 2013). De-oiled rice bran was reported to yield 10.5e11.4 % ethanol (Beliya et al, 2013). Switch grass germplasms yielded 0.082 g ethanol/g of raw biomass (Yang et al, 2009).…”
Section: Fermentation Of Hydrolyzate E Ethanol Productionmentioning
confidence: 99%